In vitro inhibition of shikimate hydroxycinnamoyltransferase by acibenzolar acid, the first metabolite of the plant defence inducer acibenzolar-S-methyl - Negrel, Jonathan; Klinguer, Agnès; Adrian, Marielle (Plant physiology and biochemistry, 2021)
Acibenzolar acid, the first metabolite formed in planta from the defence inducer acibenzolar-S-methyl (ASM), has been shown to be an inhibitor of the enzyme shikimate hydroxycinnamoyltransferase (HST), extracted from grapevine or tobacco cell suspension cultures. Using a purified recombinant Arabidopsis thaliana HST, the inhibition was found to be competitive, acibenzolar acid binding reversibly to the shikimate binding site of the HST:p-coumaroyl-CoA complex, with a Ki value of 250 μM. The other hydroxycinnamoyltransferases tested in the course of this study, using either hydroxypalmitic acid, putrescine, tyramine, or quinic acid as acyl acceptors were not, or only slightly, inhibited by acibenzolar acid. To understand the specificity of the interaction of acibenzolar acid with HST, we analyzed the structure-activity relationship of a series of benzoic or acibenzolar acid analogues, tested either as AtHST substrates or as inhibitors. This analysis confirmed previously published data on the substrate flexibility of HST and demonstrated that both the carboxyl group and the thiadiazole moiety of acibenzolar acid are playing an important role in the interaction with the shikimate binding site. Acibenzolar acid, which cannot form an ester bond with p-coumaric acid, was however a less potent inhibitor than protocatechuic or 3-hydroxybenzoic acids, which are used as acyl acceptors by HST. Our results show that the interaction of acibenzolar acid with HST, which is probably directly linked to the substrate promiscuity of HST, is unlikely to play a direct role in the defence-inducing properties of ASM in plants. •Acibenzolar acid is a competitive inhibitor of shikimate hydroxycinnamoyltransferase.•Acibenzolar acid binds reversibly to the shikimate binding site of HST.•This inhibition can be explained by the substrate promiscuity of HST.